Evaluation of Instrumental Methods for Assessing Colour Fastness (Journal of Fiber Bioengineering and Informatics, 2012)
Instrumental methods for assessing colour fastness of textile products have been standardized byorganizations such as the International Organization for Standardization (ISO) and Japanese IndustrialStandards (JIS). In addition to these, a few methods have been proposed. Despite the existence of thesemethods, fastness assessments are still being carried out in many places through visual inspection. Ina laboratory, experienced inspectors share a common understanding about degree of fastness; however,there are variations between laboratories across different countries and between experienced workers andtrainees. Therefore, in order to encourage the use of the instrumental method, four methods were re-evaluated. In the experiment, a set of fabric samples were instrumentally evaluated using four differentmethods and the samples were also visually assessed by professional inspectors in a textile testing centrein Japan. Then, the results of the instrumental methods were evaluated by comparing with the visualresults. A method proposed by Gui and Luo et al was considered to be the best model in terms of theagreement with the visual results and also this method was less influenced by the difference of colourmeasurement methods.